2017 International Symposium on Wireless Communication Systems (ISWCS) 2017
DOI: 10.1109/iswcs.2017.8108155
|View full text |Cite
|
Sign up to set email alerts
|

Mobility-aware handover strategies in smart cities

Abstract: Supporting the Internet of Things and Smart City applications is one of the most important goals in the ongoing design process of 5G cellular systems. Another trend is an increasing focus on data-driven optimization and Self-Organized Networking, in order to automate network deployments and increase performance and efficiency. This approach, however, does not fully take advantage of the data generated by the Smart City. In this work, we propose to process and use the information flowing through the network fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…A number of researches have been done where it has been found that IoT ecosystem with efficient routing and networking solution can be vital to achieving optimal performance [4,[6][7][8][9][10][11][12][13][14]. However, it has been found that classical WSN systems cannot be effective for mobile M2M communication based routing to achieve optimal performance over SCPM [12][13][14].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of researches have been done where it has been found that IoT ecosystem with efficient routing and networking solution can be vital to achieving optimal performance [4,[6][7][8][9][10][11][12][13][14]. However, it has been found that classical WSN systems cannot be effective for mobile M2M communication based routing to achieve optimal performance over SCPM [12][13][14].…”
Section: Related Workmentioning
confidence: 99%
“…Such explosively up surging demands would require more reliable and efficient data transmission system for numerous time-sensitive communication purposes such as mission-critical communication (MCC) in sensor networks, real-time monitoring and control, fire-sensing, wastemanagement system, surveillance purposes etc. [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. An upsurge in urban population and allied demands are forcing metropolitan authorises and allied agencies to exploit the different technologies and computing platform so as to avail services with assured reliability, quality and availability.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations